INNOVATIVE TECHNOLOGY OF HORIZONTAL PROTECTIVE SHIELD ARRANGEMENT USING INJECTION (Advances in Civil and Architectural Engineering, 2021)
This study focuses on developing methods of anti-contagious underground shield arrangement. The results of experimental laboratory and full-scale in situ studies of the horizontal protective shield arrangement are discussed, and the method and laboratory equipment to conduct such research are developed. Moreover, the different embodiments of the shielding apparatus are studied using bentonite, sodium hydrosilicate in combination with calcium chloride, and a waterproofing soft-elastic injection resin. The analytical and graphic dependencies of the changes of the shield filtration coefficient from different injectable formulations are presented. In conclusion, the most economically efficient technological modes of horizontal shield arrangement are the usage of soft-elastic waterproofing injection resin with drilling the wells at a 0.3 m distance from each other.